Bilateral internal thoracic artery grafting in patients with left main disease: a single-center experience. Issue 5 (August 2020) - Gordon, Amit; Nesher, Nachum; Mohr, Raphael; Pevni, Dmitry; Kramer, Amir; Ziv-Baran, Tomer; Paz, Yosef; Ben-Gal, Yanai
Abstract : Objective: We compared early and long-term outcomes between bilateral internal thoracic artery (BITA) grafting and single internal thoracic artery (SITA) grafting in patients with LM disease. Methods: We evaluated the outcomes of all patients with LM disease who underwent revascularization in our center during 1996–2011. Variables that were adjusted for in a multivariate analysis and in propensity matching included age, sex, comorbid diseases, repeat operation, the number of diseased vessels, other conduits used, the use of sequential grafting, the number of grafts constructed, and the operative era (1996–2000 vs. 2001–2011). Results: In total, 949 patients with LM disease underwent BITA grafting and 564 underwent SITA grafting during the study period. SITA patients were more often female and more likely to have comorbidities such as chronic obstructive pulmonary disease, ejection fraction <30%, recent myocardial infarction, diabetes, congestive heart failure, chronic renal failure, and peripheral vascular disease, and to have undergone an emergency operation. We found no statistically significant difference between the SITA and BITA groups in 30-day mortality (4.8% vs. 3.3%, P = 0.136), sternal wound infection (2.0% vs. 2.4%, P = 0.548), and stroke (3.2% vs. 4.4%, P = 0.234). BITA patients had improved long-term survival (70.1% vs. 52.0% p<0.001), median follow-up of 15 years. In multivariate analysis, after propensity score matching (477 matched pairs), this finding was not statistically significant ( P = 0.135). Conclusion: This study did not demonstrate a clear benefit of BITA grafts among patients with LM disease.